Pengaruh Pelatihan Stimulasi Kecerdasan Emosi Terhadap Pengetahuan dan Ketrampilan Guru TK Dalam Mengembangkan Kecerdasan Emosi Anak Didik - Nukmatus Sariri (Universitas Trunojoyo Madura, 2015)
Effect of Stimulation of Emotional Intelligence Training for Kindergarten Teachers Knowledge and Skills in Developing Students Emotional Intelligence. The Structure of the learning program in TK include the development of behavior formation and development of basic capabilities, but in terms of implementation, cognitive aspects are preferred. Emotional aspects are not a major concern when compared with other aspects, so that no matter related to it in the design of everyday activities. One of the competition required by the teacher TK namely: to understand the stages of child development and the principles of early childhood education. Based on training need assessment conducted by researchers, knowledge and skills of teachers TK less than optimal in providing the stimulation of emotional intelligence. Therefore, the purpose of this study was to determine the effect of training intelligence early childhood stimulation of the knowledge and skills of teachers TK in providing stimulation of emotional intelligence. This type of research is pre-experimental design with one group pretest posttest design. Subjects were TK teachers who have been trained on the stimulation of emotional intelligence. Result of studies suggest that stimulation of emotional intelligence training has an influence on kindergarten teachers’ skills in a stimulating early childhood emotional intelligence however, does not give effect to the teacher’s knowledge. Based on the results of data analysis using the wilcoxon signed rank test shows the value of the significance of knowledge the teacher is 0,057, while the significance value of teacher skills is 0,024.